Особливий комендант (До біографії Михайла Ковенка) - Іванущенко, Г.М. (Сумський історико-архівний журнал, 2010)
The biography of Mykhaylo Kovenko, who was a famous military and public figure, a
participant of Ukrainian revolution (1917-1921), is covered in the publication. His role in
the organization of Free Cossacks detachments and suppression of Bolsheviks’ coup in Kyiv
in 1918-1919 is also covered in the article.